2013
DOI: 10.7120/09627286.22.1.095
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the safety of collars used to attach predation deterrent devices and ID tags to pet cats

Abstract: Collar-worn deterrents reduce predation by cats while collar-mounted ID enhances return of lost animals. A perception that collars are hazardous limits adoption. We defined cases as 'collar incidents' (cat snagged its collar or caught a paw), 'collar injuries' (veterinary treatment needed for a collar incident), and 'collar deaths' (cat died), before integrating data from veterinarians, owners from the general public and 30 owners from a welfare society. Despite biases associated with components independently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…; Calver et al. ). In this study neutering, the only control strategy suggested not obviously linked to aiding wildlife populations and a largely welfare driven strategy was the most favored statement.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Calver et al. ). In this study neutering, the only control strategy suggested not obviously linked to aiding wildlife populations and a largely welfare driven strategy was the most favored statement.…”
Section: Discussionmentioning
confidence: 98%
“…This implies that even the most informed cat own-ers may not be swayed by implications for biodiversity when the cost to the cat is perceived to be high. Instead, better motivation to accept controls on cat predation may be achieved by highlighting welfare advantages (Lilith et al 2006;Toukhsati et al 2012), such as lowering the risk of road traffic accidents, poisoning, infectious diseases, fighting-related injuries, and reduced threat from wildlife interactions, which are important contributors to cat mortality and long-term welfare (Moreau et al 2003;Rochlitz 2004;Egenvall et al 2010;Calver et al 2013). In this study neutering, the only control strategy suggested not obviously linked to aiding wildlife populations and a largely welfare driven strategy was the most favored statement.…”
Section: Discussionmentioning
confidence: 99%
“…Use of collars may be limited by residual concerns about their safety (despite the relative infrequency with which quick‐release collars have been found to cause injury; Calver, Adams, Clark, & Pollock, ), practical concerns about the expense of consistently replacing quick‐release collars, lack of acceptance by cats, or perceived inefficacy at preventing hunting. There is clearly a need for more robust yet reliably safe quick‐release collars to be developed, and although collar‐mounted devices can reduce hunting efficiency (Calver, Thomas, Bradley, & McCutcheon, ; Gordon, Matthaei, & Heezik, ; Hall, Fontaine, Bryant, & Calver, ; Nelson, Evans, & Bradbury, ; Ruxton, Thomas, & Wright, ; Willson, Okunlola, & Novak, ), further work to compare the effectiveness and safety of different devices would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Death or injury of cats in these events had considerable financial and emotional costs to owners in one region of the UK (see Rochlitz, 2004a;. Given the high frequency of road accident trauma for cats elsewhere (Engenvall et al, 2009, Calver et al, 2013 financial and emotional costs are likely to be widespread. It can also be difficult to reunite lost cats with their owners.…”
Section: Introductionmentioning
confidence: 99%
“…If an inexpensive collarmounted device could reduce roaming, then predation, disease transmission and general nuisance attributed to pet cats could be reduced, as well as the risks of road accidents, fighting and unwanted litters. While owners may have reservations about the safety of collars (Lord et al, 2010), the risk of serious injury or death is low for correctly fitted and maintained safety collars (Brinkley, 2007;Lord et al, 2010;Calver et al, 2013).…”
Section: Introductionmentioning
confidence: 99%